2007
DOI: 10.1007/978-3-540-73279-2_84
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Caption Editing System with Presentation Software

Abstract: There is an increasing number of rich content that includes audio and presentations. It is important to caption these contents to assure accessibility for hearing impaired persons and seniors. Initially, we conducted a survey and found that the combination of video with audio, captions, and presentation slides (hereafter "multimedia composite") is helpful in understanding the content. Also our investigation shows that the availability of captioning is still very low and therefore there is a strong need for an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Another method used to create accessible materials for presentations follows the multimedia composite approach of Miyamoto, Arakawa, and Takizawa (2007), which uses audio, captions, and slide-deck materials created through IBM CES studio. Software such as Adobe Animate CC allows for the creation of captions with video in FLV and Flash.…”
Section: Captioning Technologies For Enhancing the Reach Of Presentatmentioning
confidence: 99%
See 1 more Smart Citation
“…Another method used to create accessible materials for presentations follows the multimedia composite approach of Miyamoto, Arakawa, and Takizawa (2007), which uses audio, captions, and slide-deck materials created through IBM CES studio. Software such as Adobe Animate CC allows for the creation of captions with video in FLV and Flash.…”
Section: Captioning Technologies For Enhancing the Reach Of Presentatmentioning
confidence: 99%
“…YouTube’s automatic captioning function can also be substituted for CES studio. Based on their surveys of senior citizens and the disabled, Miyamoto et al (2007) found that their respondents saw the composite approach as useful for all ages in the learning process. Of special interest to this study was the use of speaker notes in presentation software that allows for either separate notes to be hosted alongside the presentation or for captioning software to create captions from the notes themselves.…”
Section: Captioning Technologies For Enhancing the Reach Of Presentatmentioning
confidence: 99%